Syariah accounting, sustainable finance, and financial performance: evidence from Indonesian Islamic banks - Didin Purniawan (Journal of Islamic Accounting and Finance Research, 2026)
Purpose - This study examines the effect of Shariah Accounting (Islamic Social Reporting, Corporate Social Responsibility, and productive zakat/waqf) and Sustainable Finance (green financing, green sukuk, and green project financing) on the financial performance of Islamic banks in Indonesia. Method - A quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM) was applied using secondary data from the annual reports of Islamic banks in Indonesia during 2021–2024, selected through purposive sampling. Result - The findings indicate that CSR, productive zakat and waqf, and green project financing significantly reduce the operational efficiency ratio (BOPO), reflecting improved cost efficiency. Green financing negatively affects Return on Assets (ROA), implying a short-term trade-off between profitability and sustainability. Meanwhile, Islamic Social Reporting (ISR) and green sukuk show no significant influence on any financial performance indicators. Implication - These results highlight the importance of embedding ethical values and sustainability practices into the strategic management of Islamic banks to achieve a balance between social responsibility and financial objectives. Originality - This study provides novelty by simultaneously testing the integration of Islamic social finance and sustainable finance instruments within a comprehensive empirical model in Indonesia.